Influence of the satisfaction and the perceived value related to the “Word of Mouth” in costumers of sports center - García Pascual, F.; Molina García, N.; Mundina Gómez, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
One of the main objectives of sports services is to retain users as long as possible in this service. For this reason, since the beginning of the literature on sports management, which analyzes the different management variables, more and more works appear that try to provide information related to this objective. Within the future intentions of the users, the recommendation is one of the main factors to be able to analyze the future behaviors of these users. For this reason, this research tries to analyze which is the influence of the satisfaction and the perceived value of the users, on the "Word of Mouth", that is, how these two variables influence the future recommendations of the same users. In this way, to provide different sports services, and sports managers in particular, valuable information to obtain loyal customers to the service.